(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper examined the gaps in the implementation of population policies in Punjab, Pakistan, focusing on governance, financing, service delivery, supply chains, sociocultural factors, and monitoring systems. Despite the Punjab Population Policy (2017) and national reproductive health initiatives, progress toward population stabilization remains limited. Using a quantitative design with 300 respondents, multiple regression and ANOVA analyses were applied. Results indicated that governance, service delivery, supply chains, and monitoring systems were the strongest predictors of policy effectiveness, with financing and sociocultural factors also contributing. Together, these explained 62% of the variance in perceived effectiveness. However, ANOVA showed governance alone had no significant impact, highlighting the importance of integrated systemic and cultural factors. The study concludes that addressing these multidimensional gaps requires a holistic, coordinated approach to strengthen population policy outcomes in Punjab.